Sistema de leito de drenagem e sedimentador como solução para redução de volume de lodo de decantadores e reuso de água de lavagem de filtros - Fontana, Antonio Osmar (2004)
Water supply systems utilize, in most cases, conventional Water Treatment Plants (WTPs). These plants use alum and ferric salts in their coagulation process, and produce residues (sludge) mainly in filter systems and decanter tanks. The produced residues may be toxic to man and are usually disposed of on environment without any kind of treatment, therefore causing pollution. They present fluid characteristic with low solid content and great amount of water. Such characteristic hampers its transportation and proper disposal. The Cardoso plant used to fit the profile of pollutant, dumping its untreated sludge directly into a nearby stream. As a solution to this problem a system with a drainage bed for the sludge from decanter tank and a sedimentation tank for the backwash water from filters have been built. The system was built within the plant area itself. The drainage bed consists of a brick tank with a gravel layer support coated with a geotextile. The solid mass from the dewatered sludge showed adequate conditions as far as characteristics necessary for its final transportation and proper disposal. The water drained from sludge (effluent) is sent to the sedimentation tank. The turbidity, solids and COD were greatly reduced. The system was designed for a less than 30 days utilization period. The sedimentation tank consists of a fiberglass vase installed in a position that allows it to also receive the effluent from the drainage bed. The clarified water is recirculated to the influent of the water treatment plant and the solids are pumped to the drainage bed together the sludge from decanter tank. The system s operation does not require much labor and equipment. The aim of the research carried out was to design and analyze the drainage bed behavior according to prototype developed in the PROSAB 2 research Tema IV, integrated with Sedimentation Tank. Such integrated technology is an effective solution for the great majority of Water Treatment Plants with available areas. It is recommended that such system (Drainage bed and Sedimentation Tank) to be implemented should be always arranged to properly each individual Water Treatment Plant. Further studies should be also made on alternative of throwing clarified water straight from decanter tank to filters before dumping the sludge into drainage bed.